2014
DOI: 10.1186/1743-0003-11-122
|View full text |Cite
|
Sign up to set email alerts
|

Continuous and simultaneous estimation of finger kinematics using inputs from an EMG-to-muscle activation model

Abstract: BackgroundSurface electromyography (EMG) signals are often used in many robot and rehabilitation applications because these reflect motor intentions of users very well. However, very few studies have focused on the accurate and proportional control of the human hand using EMG signals. Many have focused on discrete gesture classification and some have encountered inherent problems such as electro-mechanical delays (EMD). Here, we present a new method for estimating simultaneous and multiple finger kinematics fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
81
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(93 citation statements)
references
References 29 publications
4
81
0
2
Order By: Relevance
“…For within-movement generalization, the overall decoding performance was R 2 = 0.70 ± 0.04 for LR, and R 2 = 0.79 ± 0.04 for KRR, which is higher than R 2 = 0.55 reported by Smith et al [7]. Comparison to other studies is more challenging, due to differences in electrode placement [8,9].…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…For within-movement generalization, the overall decoding performance was R 2 = 0.70 ± 0.04 for LR, and R 2 = 0.79 ± 0.04 for KRR, which is higher than R 2 = 0.55 reported by Smith et al [7]. Comparison to other studies is more challenging, due to differences in electrode placement [8,9].…”
Section: Discussionmentioning
confidence: 67%
“…Previous work has shown that the use of nonparametric methods, such as Gaussian Process regression, can improve decoding performance, especially in the case of limited availability of training data [9]. We argue, however, that any algorithmic comparison should be assessed on both within-, as well as across-movement generalization.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A few studies have tackled the problem of estimating finger movement from sEMG [82]. In [83], a time-delayed neural network was used to estimate finger joint angles while [72] showed that a Gaussian process regression model outperformed the neural network one. Gaussian mixture model on top of the RNN, we show that we can build a probabilistic model that can successfully reconstruct hand kinematics.…”
Section: Introductionmentioning
confidence: 99%
“…Non-invasive surface electromyogram (sEMG) recordings on the forearm contain useful information for decoding muscle activity and hand kinematics [71,72]. sEMG has been used by researchers to develop intuitive robotic prosthesis interfaces either via pattern recognition using physiological features or via classical control schemes [73,74].…”
Section: Introductionmentioning
confidence: 99%